Visitors' visual responses towards daylighting in historic museum galleries in Malaysia - Sheikh Ahmad, Sabarinah; Ahmad, Noraini; Talib, Anuar; Yaman, Rostam (Association of Malaysian Environment-Behaviour Researchers (AMER), 2014)
Daylighting in historic buildings is not an easy criterion to manage as natural light fluctuates according to the sky conditions. Many visual comfort issues are associated to high illuminance levels, glare, high contrast areas, lack of visual adaptation and overheating. Daylighting in urban museum galleries in Malaysia remained an area that is lacking in knowledge. This study aims to evaluate the visitors’ visual responses and satisfaction levels towards daylighting in historic museums under the tropical sky conditions. This study focuses on evaluating the measured indoor illuminance levels and visitors’ visuals responses of the daylighting conditions. The locations of the survey were at four selected historic museum interior modules in Malaysia. These adaptive reuse buildings functions as museums after being converted from other functions. The evaluation of the performance of daylighting applied in Malaysian historic museums was based on sidelighting design in four types of gallery space: balcony, corridor, compartmental and open planning. The research studies were performed through field measurements of the illumination and visitors survey during operation hours of the respective museums. Observations of the vote count percentages of the visitors’ responses were under three consecutive daylight condition; 09.00h to 11.59h (morning); 12.00h to 14.59h (afternoon) and 15.00h to 16.59h (evening). The measurements employed data logger management system, light sensors at test points at showcases and display panels. The questionnaire survey evaluated the users’ observation and satisfaction in relation to daylight conditions at two different placements of showcases (against window wall-AWW and opposite window wall-OWW). Recording and close monitoring of the responses were via questionnaires issued to them. Results revealed that the measured illuminance assessment and evaluation indicated that the display placement affected the daylight distribution pattern. Meanwhile, assessment on the visitors’ perception demonstrated that the daylighting pattern affected the visitors' viewing satisfaction. The study introduces the issues of daylight distributions and the visitors’ visual perception and satisfaction in relation to the exhibits and interior configuration of the museums. The study found significant effects of the exhibit condition and interior design parameters on indoor daylight performance and visual comfort. The results of this study could contribute to the planning of appropriate daylighting environment to minimise visual discomfort in historic museums context.